Development and Evaluation of an eLearning Training Module to Improve United Kingdom Secondary School Teachers’ Knowledge and Confidence in Supporting Young People Who Self-Harm - Price, Claire; Satherley, Rose-Marie; Jones, Christina J.; John, Mary (Frontiers in Education, 2022)
Background: Self-harm is a major public health concern with evidence suggesting that the rates are higher in the United Kingdom that anywhere else in Europe. Increasingly, policy highlights the role of school staff in supporting young people who are self-harming, yet research indicates that school staff often feel ill-equipped to provide support and address self-harm behaviours. Here, we assess the impact of a bespoke eLearning module for UK secondary school teachers on teacher’s actual and perceived knowledge of self-harm, and their self-reported confidence in supporting and talking to young people who self-harm. Methods: Twenty-one secondary schools across the West Midlands and Southwest of England were invited to complete a 30-minute web-based eLearning module on self-harm in schools. Participants completed pre-and post-intervention measures. Results: One-hundred and seventy-three teachers completed the eLearning, and pre-and post-measures. The eLearning significantly enhanced participants’ perceived knowledge, actual knowledge, and confidence in talking to and supporting young people who self-harm. The majority of participants (90.7%) felt that eLearning was a good way to receive training. Conclusion: The 30-minute eLearning module was rated highly and may be an effective way to increase secondary school teachers’ knowledge of self-harm, and confidence in supporting and talking to young people who self-harm.